Nonsteroidal anti‐inflammatory drugs (NSAID) and aspirin for preventing recurrence and metachronous colorectal carcinomas in patients previously treated for colorectal cancer - Latchford, Andrew R (Cochrane Database Syst Rev, 2020)
This protocol for a Cochrane Review has been withdrawn.    Reason for withdrawal: Authors have made no progress with this protocol in 3 years. New authors are being sought to take over this protocol.    The protocol is being withdrawn by Kristoffer Andresen, Managing Editor ‐ Cochrane Colorectal Group. The authors have agreed to the withdrawal.